2003
DOI: 10.1016/s0896-6273(03)00194-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional Topography of Connections Linking Mirror-Symmetric Maps in the Mouse Olfactory Bulb

Abstract: In rodents, each main olfactory bulb contains two mirror-symmetric glomerular maps, a feature not found in the initial topographic maps of other sensory systems. Targeting tracer injections to identified glomeruli revealed that isofunctional odor columns-translaminar assemblies connected to a given glomerulus-were specifically and reciprocally interconnected through a mutually inhibitory circuit with exquisite topographic specificity. Thus, instead of containing two mirror-symmetric maps, we propose that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 55 publications
(7 reference statements)
3
95
0
Order By: Relevance
“…The isofunctional (lateral and medial) glomeruli located within each OB are reciprocally connected by interneurons that may contribute to the refinement of odorant information in the OB (Lodovichi et al, 2003). Our preliminary data regarding rheological simulation indicates that temporal and spatial distribution patterns of an odorant in the nasal cavity are quite different depending on the breathing conditions (Y.…”
Section: Discussionmentioning
confidence: 86%
“…The isofunctional (lateral and medial) glomeruli located within each OB are reciprocally connected by interneurons that may contribute to the refinement of odorant information in the OB (Lodovichi et al, 2003). Our preliminary data regarding rheological simulation indicates that temporal and spatial distribution patterns of an odorant in the nasal cavity are quite different depending on the breathing conditions (Y.…”
Section: Discussionmentioning
confidence: 86%
“…Neural tracer injections were performed as described previously (Lodovichi et al, 2003). Briefly, for in vivo injections, mice were anesthetized with an intraperitoneal injection of 100 mg/kg ketamine hydrochloride and 10 mg/kg xylazine hydrochloride and maintained with 100% oxygen supplemented with a 1.0 -3.0% isofluorane gas inhalant.…”
Section: Methodsmentioning
confidence: 99%
“…This organization is less clear in the olfactory system in which olfactory sensory neurons (OSNs) that express a common odorant receptor are broadly scattered throughout the nasal turbinates but coalesce to form glomerular maps as their axons reach the bulb (Ressler et al, 1994;Vassar et al, 1994). Recent studies have shown that a second-order map also exists that precisely links the glomerular maps within each bulb through a reciprocal projection mediated by external tufted cells (ETCs) (Schoenfeld et al, 1985;Belluscio et al, 2002;Lodovichi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Each glomerulus is innervated by 20 -50 mitral/tufted cells, each of which innervates a single glomerulus with a single primary dendrite. Tufted cells project axon branches to the isotypic olfactory columns on the mirrorsymmetrical positions, forming intrabulbar connections (Lodovichi et al 2003). In addition to the excitatory neurons, there are several types of inhibitory interneurons, the periglomerular cells and granule cells (reviewed in Wilson and Mainen 2006).…”
Section: Olfactory Circuits In the Brain Axonal Convergence And The Tmentioning
confidence: 99%